System emerytalny i jego zmiany w Polsce w kontekście deficytu budżetowego oraz długu publicznego w latach 1999–2014 - Ciak, Jolanta; Kołosowska, Bożena (Kwartalnik Kolegium Ekonomiczno-Społecznego. Studia i Prace, 2015)
Since January 1999 a new pension system based on the reformed Social InsuranceInstitution (ZUS) and open pension funds (OFE) has been in force. The reformsdid not concern all the insured in ZUS uniformly, due to its scope and costs. The aim of the article is to present the changes in the Polish national pension systemand their influence on the public finance including the state budget. The influenceis considerable due to the long-lasting imbalance in the state budget and theaccumulating public debt. The authors discern that the changes suggested by thegovernment can be assessed as the choice between being responsible for presentand being responsible for the future. Thus the effects of the current changesin the pension system are moved to the future generations and the sources of theirfinancing, whether they are in the form of higher taxes, smaller public expenditureor higher public debt, will depend on the future economic policy includingthe financial policy.